Lesson Study: A Systematic Routine to Enhance Students’ Social Character and Creative Writing Abilities - Istikharoh, Lutfi; Kusumastuti, Dyah; Riswanto, Riswanto; Masruroh, Yulfah; Setiowati, Setiowati; Sarno, Sarno (Universitas Siliwangi, 2024)
To effectively educate the future generation, instructors must keep up with the fast-paced global changes by being updated on advancements in science, technology, and educational trends. A very effective lecturer-teacher partnership program (KDS) that utilises lesson study can accomplish this objective. The primary objectives of the KDS are to foster educational innovation, facilitate academic research and publication, and actively involve educators and students in the field of education. The lesson study was carried out within the English Language Education Study Program, including two classes from the third semester of the Creative Writing Course, IIIA and IIIB. The program aims to cultivate and improve students’ social comportment and creative writing skills. Two iterations were carried out, and there was a noticeable augmentation in the students’ sociability from the first iteration to the second. Throughout Cycle 1, students exhibited tolerance and the ability to appreciate their peers’ perspectives. They enthusiastically participated and interacted during the group work. Their average achievement percentage was 67.47% and witnessed a remarkable increase of 85.14% in Cycle 2. The level of collaboration and unity in project completion rose from 57.61% in cycle 1 to 88.99% in cycle 2. The students’ receptiveness to the learning environment significantly increased from 52.09% in cycle 1 to 85.14% in cycle 2. The cognitive domain has significantly enhanced knowledge acquisition, particularly in students’ creative writing skills. The proportion of students in IIIA, exhibiting this proficiency increased from 37% in cycle 1 to 77% in cycle 2. In class IIIB, there was a significant 40% surge, as the percentage escalated from 43% to 83%. Thus, adopting lesson study allows students to improve their social behaviour and support their writing ability. Keywords: Creative writing; interactive learning; social character building; collaboration.